Self-Efficacy and Active Listening Skills of Peer Counselors in Preventing Mental Health Problems as an Impact of Covid-19 Pandemic - Fitriana, Qurrota A’yuni; Rosyidi , Hamim (International Conference on Sustainable Health Promotion, 2021)
Mental health problems are becoming a serious impact caused by the Covid 19 pandemic. Learning problems, general stress to somatic problems are psychosocial problems dominating from childhood to adulthood. The existence of early treatment is needed to prevent mental health problems, such as conducting peer counseling. Peer counseling is carried out by peer counselors who had a role in assisted and helped in problem-solving related to mental health. They are expected to have self-confidence and mastered basic techniques in counseling such as active listening skills. This study aims to determine the role of self-efficacy and active listening skills in peer counselors in their role in preventing mental health problems due to the Covid 19 pandemic. The research subjects were 27 people who were students/graduates majoring in psychology/counseling guidance and had attended peer counseling training. The research method used is a quantitative method with hypothesis testing using multiple regression analysis. The results showed that the self-efficacy and active listening ability of peer counselors partially had no role in preventing mental health problems with values ​​of Sig 0.473 > 0.05 and Sig 0.985 > 0.05, respectively. Simultaneously, self-efficacy and active listening ability of peer counselors also did not show a significant role with a Sig F value of 0.720 > 0.05. However, it was found that the effect of self-efficacy and active listening ability on peer counselors together on the prevention of mental health problems due to the COVID-19 pandemic was 2.7%.